Benefits of Monitoring and Evaluation for Improvement Quality Teacher on Process Learning - Nasution, Ika Harni; Sihombing, Rina Lena; Elfrianto, Elfrianto (Indonesian Journal Education, 2023)
This research method is a qualitative method with a library study approach research). Data collection is carried out by searching for sources of information and summarizes information from various sources, including books, journals, and research has existed before. which has a relationship with monitoring and evaluation of enhancement quality Teacher. Study This aim so that reader can obtain deeper understanding of the benefits of monitoring and evaluation for improvement quality Teacher on process learning, started with look for and analyze literature relevant to the monitoring and evaluation research used for analyze. The results of this research discuss monitoring and evaluation education, Miscellaneous monitoring evaluation on education, characteristics monitoring and evaluation in education, and the benefits of monitoring and evaluation improving teacher quality. Monitoring helps identify obstacles teachers and provide appropriate interventions. Evaluation provides an overview of achievements Teacher to standard, support development professional, form base for increase quality teaching and results learning student in a way sustainable.